ETS-related gene (ERG) undermines genome stability in mouse prostate progenitors via Gsk3β dependent Nkx3.1 degradation. (28th May 2022) - Lorenzoni, Marco; De Felice, Dario; Beccaceci, Giulia; Di Donato, Giorgia; Foletto, Veronica; Genovesi, Sacha; Bertossi, Arianna; Cambuli, Francesco; Lorenzin, Francesca; Savino, Aurora; Avalle, Lidia; Cimadamore, Alessia; et al.
Abstract: 21q22.2–3 deletion is the most common copy number alteration in prostate cancer (PCa). The genomic rearrangement results in the androgen-dependent de novo expression of ETS-related gene ( ERG ) in prostate cancer cells, a condition promoting tumor progression to advanced stages of the disease. Interestingly, ERG expression characterizes 5–30% of tumor precursor lesions – High Grade Prostatic Intraepithelial Neoplasia (HGPIN) - where its role remains unclear. Here, by combining organoids technology with Click-chemistry coupled Mass Spectrometry, we demonstrate a prominent role of ERG in remodeling the protein secretome of prostate progenitors. Functionally, by lowering autocrine Wnt-4 signaling, ERG represses canonical Wnt pathway in prostate progenitors, and, in turn, promotes the accumulation of DNA double strand breaks via Gsk3β-dependent degradation of the tumor suppressor Nkx3.1. On the other hand, by shaping extracellular paracrine signals, ERG strengthens the pro-oxidative transcriptional signature of inflammatory macrophages, which we demonstrate to infiltrate pre-malignant ERG positive prostate lesions. These findings highlight previously unrecognized functions of ERG in undermining adult prostate progenitor niche through cell autonomous and non-autonomous mechanisms. Overall, by supporting the survival and proliferation of prostate progenitors in the absence of growth stimuli and promoting the accumulation of DNA damage through destabilization of Nkx3.1, ERG could orchestrate the prelude to neoplastic transformation. Highlights: Expression of ERGM40 in mouse prostate organoids promotes their survival and growth in the absence of Egf. ERGM40 alters the extracellular signaling network of mouse prostate organoids. Canonical Wnt pathway is substantially reduced in ERG + prostate organoids due to decreased autocrine signaling of Wnt4. Gsk3b promotes Nkx3.1 proteolysis and, in turn, accumulation of double strand breaks in ERG + prostate organoids. Paracrine signaling of ERG + prostate organoids modulates Arginase 1 expression in M1-polarized macrophages.